EXTRACURRICULAR SERVICE MASTERING MODEL FOR SCHOOL PHYSICAL EDUCATION TEACHERS - Mezinov, V.N.; Zakharova, M.A.; Karpacheva, I.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze and prioritize the key institutional and pedagogical provisions for the extracurricular service competency formation in future school physical education teachers. Methods and structure of the study. The extracurricular service mastering model testing experiment was run at Institute of Physical Education, Sports and Life Safety of the Bunin Yelets State University in 2019-2021. We sampled the 2-4-year students (n=162) majoring in the Physical Education and Life Safety specialties under 44.03.05 Pedagogical Education discipline; and split them up into EG (n=80) and RG (n=82). Results and conclusion. The extracurricular service mastering model testing experiment found its benefits for the future school physical education teachers in the following components: – Motivations and values in the extracurricular service providing domain; – Practical learning and training to form due extracurricular service knowledge and skills; – Experience in complementing the regular physical education curricula by interactive technologies (case studies, business games, brainstorming, focused training) to facilitate progress of schoolchildren in the extracurricular service formats; - Establishing social partnerships with the relevant educational organizations for internships, and with the relevant municipal agencies; and - Stimulating reflection to analyze the own and students’ progress in the extracurricular service process versus the past and present benchmarks and practical experiences to fairly rate, analyze and find solutions for every new situation in the extracurricular service process. Success of an extracurricular service heavily depends on the actual professional motivations and values, didactic provisions, students’ and teachers’ personal progress agendas, teaching staff, applied interactive technologies, and generally on a progress facilitating climate that should be friendly and cooperative to effectively address every issue and mission in the extracurricular training process.